Mechanical differences between barbell and body optimum power loads in the jump squat exercise - Loturco, I.; Pereira, L. A.; Zanetti, V.; Kitamura, K.; Cal Abad, C. C.; Kobal, R.; Nakamura, F. Y. (Journal of Human Kinetics, 2016)
This study compared the values of bar-peak force (PFBar) and power (PPBar), body-peak force (PFBody) and power (PPBody) and bar-mean propulsive power (MPPBar) in different jump-squat (JS) conditions: unloaded condition (UC); bar-loaded condition (BLC) and optimum bar-MPP condition (OBC). Twenty-five soccer players performed the JS using a bar with negligible mass (UC), using the Smith-machine bar (BLC) and using the load capable of maximizing the bar-MPP (OBC). The PFBody was significantly higher in the UC (2847.9 ± 489.1 N) than in the OBC (2655.4 ± 444.3 N). The UC presented greater PPBody (3775.9 ± 631.5 W) than the BLC (3359.7 ± 664.3 W) and OBC (3357.8 ± 625.3 W). The OBC presented higher values of PFBar, PPBar and MPPBar (676.2 ± 109.4 W) than the BLC (MPPBar = 425.8 ± 53.7 W) (all p < 0.05). In the OBC (compared to the UC), the body peak-power presented a reduction of ˜ 11%, while generating bar-power output from ˜ 59 to 73% higher than the BLC. While the fact that the body-peak power is maximized in the UC denotes a mechanical phenomenon, the bar-optimum load represents an intensity at which both components of the power equation (force and velocity) are optimized. This has important implications for sports training.